Book Reviews (The Muslim world, 1954)
Book reviewed in this article: Muhammad at Mecca. By W. Montgomery Watt Geschichte der Islamischen Länder. Erster Abschnitt Mystique Naturelle et Mystique Surnaturelle en Islam. By Louis Gardet Quelques Textes LSüfis Concernant L'“Extase”. By Louis Gardet The Baptistre de Saint Louis, a Masterpiece of Islamic Metal Work. By D. S. Rice. The Arab World. By Nejla Izzedin The Numismatic History of Late Medieval North Africa. By Harry W. Hazard